Diversity of Conditions and Forms of Learning Interaction as a Factor of Academic Performance - Kosaretsky, S.G. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2024)
In light of the increasing diversity within schools and classrooms, the issue of risks and opportunities for the success of every child is becoming increasingly significant. This article offers an overview of the current research on the relationship between the diversity of school and classroom compositions and the academic achievement of students. It also explores approaches to organizing cooperative learning and peer tutoring in heterogeneous classes. The possibilities and limitations of existing research in educational policy and pedagogical practice are examined. The potential of cultural-historical psychology, particularly the socio-genetic psychology of educational interactions, is substantiated for further research. В статье представлен обзор актуального состояния исследований связи вариативности составов школ (классов) по социальным, академическим, этническим характеристикам, особым образовательным потребностям учащихся с образовательными результатами, а также подходов к организации развивающего учебного взаимодействия сверстников в гетерогенных классах. Раскрываются возможности и ограничения существующих исследований для образовательной политики и педагогической практики. Обосновывается потенциал культурно-исторической психологии в целом и социально-генетической психологии учебных взаимодействий - в частности, для дальнейших исследований вопроса.